2015
DOI: 10.1111/cts.12263
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Implications of Eukaryotic Initiation Factor 3f and Her‐2/neu Expression in Gastric Cancer

Abstract: Background : To detect the expression of eIF3f and human epidermal growth factor receptor 2 (Her-2)/neu in gastric cancer (GC), correlation with their clinicopathological parameters and the relationship of eIF3f and Her-2/neu in the occurrence and development of GC. Methods : A total of 195 gastrectomy specimens with stage I to III were examined for eIF3f expression by immunohistochemistry and for Her-2/neu expression by fl uorescence in situ hybridization (FISH) with the median follow-up period of 38 months. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
3
0
2
Order By: Relevance
“…Previous studies have demonstrated that eIF3d was overexpressed in several human cancers, such as prostate cancer, 15 colon cancer, 16 and melanoma, 17 while also resistant to chemotherapy. 20 There have been recent studies on expression of other subunits of eIF3 in GC 9 , 25 ; however, the role of eIF3d in GC remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that eIF3d was overexpressed in several human cancers, such as prostate cancer, 15 colon cancer, 16 and melanoma, 17 while also resistant to chemotherapy. 20 There have been recent studies on expression of other subunits of eIF3 in GC 9 , 25 ; however, the role of eIF3d in GC remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The high expression of eIF3d is associated with a poor prognosis for patients with gastric cancer 14 . eIF3f expression is significantly decreased in many human cancers, and the decreased expression of eIF3f is a significant factor for a poor prognosis for gastric cancer patients 1517 .…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a discrepancy regarding eIF3f's role in cancer. Studies showed that high expression of eIF3f correlated with advanced gastric tumor stages and likelihood of recurrence [ 31 ] just like CRC, while eIF3f expression is significantly decreased in human pancreatic adenocarcinoma and melanoma, [ 32 ] and eIF3f inhibits tumor growth in cervical cancer model. [ 33 ] Yet, it is not clear how this discrepancy occurs.…”
Section: Discussionmentioning
confidence: 99%